2020
DOI: 10.1590/0037-8682-0013-2020
|View full text |Cite
|
Sign up to set email alerts
|

Human fusariosis: An emerging infection that is difficult to treat

Abstract: Fusarium spp. has been associated with a broad spectrum of emerging infections collectively termed fusariosis. This review includes articles published between 2005 and 2018 that describe the characteristics, clinical management, incidence, and emergence of these fungal infections. Fusarium solani and F. oxysporum are globally distributed and represent the most common complexes. Few therapeutic options exist due to intrinsic resistance, especially for the treatment of invasive fusariosis. Therefore, the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 59 publications
(64 reference statements)
0
86
0
1
Order By: Relevance
“…has been noted previously (28). Moreover, Fusarium incarnatum was the most common species among fusariosis cases (3/6), which is unlike previous studies that reported F. solani complex (comprising ∼40-60% of infections), followed by F. oxysporum as the most common species in immunocompromised patients other than COVID-19 (29). Interestingly, we also found D. foeniculina in the BAL sample of one of the CAPMI cases, which is known for being a plant pathogen.…”
Section: Discussionmentioning
confidence: 55%
“…has been noted previously (28). Moreover, Fusarium incarnatum was the most common species among fusariosis cases (3/6), which is unlike previous studies that reported F. solani complex (comprising ∼40-60% of infections), followed by F. oxysporum as the most common species in immunocompromised patients other than COVID-19 (29). Interestingly, we also found D. foeniculina in the BAL sample of one of the CAPMI cases, which is known for being a plant pathogen.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, Fusarium sp. has been reported among the emerging causes of opportunistic mycoses in humans and animals [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Defects in innate immune responses, including neutropenia, alveolar macrophage dysfunction, and mutations in STAT3 (resulting in autosomal dominant hyper IgE syndrome) and impaired NAPDH oxidase activity facilitate the development of pulmonary, and in some cases invasive, aspergillosis (8), whereas mutations in the gene for CARD9 (signaling adaptor protein for the C-type lectin receptor) results in increased susceptibility to many types of fungal infection, including dermatophytosis (9,10). The reasons for the increased incidence of fungal infections over recent decades are beyond the scope of this manuscript and readers are directed to several excellent reviews on the subject (3,4,7,(11)(12)(13)(14)(15). Fungi are ubiquitous throughout nature and we are constantly exposed to these microbes from the environment via inhalation, ingestion or on epithelial surfaces including the skin and mucosae (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%